Early cretaceous igneous activities in the north flank of the North China Craton: the Shouwangfen complex example. Issue 6 (12th April 2020) - Dong, Pengsheng; Dong, Guochen; Santosh, M.; Sun, Zhuanrong; Li, Huawei; Wang, Shushu; Wang, Weiqing
ABSTRACT: The Early Cretaceous igneous complexes in the north flank of the North China Craton (NCC) provide a window to investigate the Mesozoic magmatism in the NCC. Here we report the precise timing of Early Cretaceous magmatism and magma petrogenesis of the different rock types in the north flank of the NCC based on petrology, mineral chemistry, geochemistry, zircon geochronology and Sr-Nd isotopes. Zircon U-Pb dating reveals that the Shouwangfen complex was crystallized at 130–128 Ma. The rocks display enrichment in large ion lithophile elements (LILE) and LREE, and depletion in high field strength elements (HFSE) and HREE, with relatively high Sr/Y and La/Yb values, typical of subduction-related magmatic rocks. The mafic microgranular enclaves show typical igneous textures, acicular apatites, sieve-texture of plagioclase phenocrysts and overgrowth of amphibole around the pyroxene, corresponding to magma mixing and mingling and thermal exchange. The quartz monzonites display normal zoning of the plagioclase, low and homogeneous ε Nd( t ) values and linear co-variations in two-component diagrams. The quartz monzodiorites are characterized by high and homogeneous ε Nd( t ) values. Petrologic feature and geochemical data suggest that the quartz monzonites represent lower crustal magma with minor contribution of enriched melt of the sub-continental lithospheric mantle (SCLM), followed by fractional crystallization. The mafic microgranular enclaves were sourced from enriched SCLM, followed by mixing and mingling with the host quartz monzonitic magma. The quartz monzodiorites are mainly SCLM-derived and subsequently mixed with lower crust melts. The high water contents (≥3%) of these Early Cretaceous igneous complexes suggests a hydrous SCLM beneath the NCC. The Early Cretaceous igneous complexes formed within an extensional tectonic setting which were related to the retreat and dehydration of the paleo-Pacific slab. The hydration of the lithosphere induced extensive crust-mantle interaction and large-scale water-rich magmatism, leading to lithospheric thinning in the NCC during the Mesozoic. Graphical Abstract: uf0001